Imaging Fibrogenesis in a Diet-Induced Model of Nonalcoholic Steatohepatitis (NASH). (1st December 2019) - Hartimath, S. V.; Boominathan, R.; Soh, V.; Cheng, P.; Deng, X.; Chong, Y. C.; Yong, F. F.; Tan, P. W.; Han, W.; Robins, E. G.; Goggi, J. L.
Abstract : Purpose . Liver fibrosis is the hallmark of chronic nonalcoholic steatohepatitis (NASH) and is characterised by the excessive deposition of extracellular matrix proteins. Early detection and accurate staging of liver fibrosis is critically important for patient management. One of the earliest pathological markers in NASH is the activation of hepatic stellate cells (HSCs) which may be exploited as a marker of fibrogenesis. Activated HSCs secreting factors such as integrin α v β 3 propagate fibrosis. The purpose of the current study was to assess the utility of the integrin α v β 3 imaging agent [ 18 F]FtRGD for the early detection of fibrosis in a diet-induced model of NASH longitudinally using PET imaging. Procedures . Mice were fed with either standard chow diet (SD), high-fat diet (HFD), or a choline-deficient, L-amino acid-defined high-fat fibrogenic diet (CDAHFD) to mimic the clinical pathology of liver disease and followed longitudinally for 10 weeks to assess the development of liver fibrosis using [ 18 F]FtRGD positron emission tomography (PET) imaging. Standard blood biochemistry, histological measures, and qPCR were used to quantify integrin α v β 3, smooth muscle actin, and collagen types 1 and 6 to assess the extent of NASH pathology and accurately stage liver fibrosis. Results . The CDAHFD fibrogenic diet predictably developed hepatic inflammation and steatosis over the 10 weeks studied with little NASH pathology detected in high fat diet-treated animals. Stage 1 fibrosis was detected early by histology at day 21 and progressed to stage 2 by day 35 and stage 3 by day 56 in mice fed with CDAHFD diet only. Noninvasive imaging with [ 18 F]FtRGD correlated well with integrin α v β 3 and was able to distinguish early mild stage 2 fibrosis in CDAHFD animals compared with standard chow diet-fed animals at day 35. When compared with high fat diet-fed animals, [ 18 F]FtRGD was only able to distinguish later moderate stage 2 fibrosis in CDAHFD animals at day 49. Conclusions . The diet-induced progression of liver fibrosis was confirmed using histology and correlated well with the mRNA of integrin α v β 3 and extracellular matrix protein expression. [ 18 F]FtRGD showed very good correlation between liver uptake and integrin α v β 3 expression and similar detection sensitivity to the current clinical gold standard modalities for staging of liver fibrosis.